Modeling of an Impact of Thin Insulating Film on the Electrode Surface on Discharge Ignition in Mercury Illuminating Lamps at Low Ambient Temperatures - G. G. Bondarenko; M. R. Fisher; V. I. Kristya; P. Żukowski (Приборы и методы измерений, 2019)
The mixture of argon and mercury vapor with temperature-dependent composition is used as the background gas in different types of gas discharge illuminating lamps. The aim of this work was to develop a model of the low-current discharge in an argon-mercury mixture at presence of a thin insulating film on the cathode and to investigate the influence of film on the discharge ignition voltage at low ambient temperatures. When discharge modeling, we used the obtained earlier expression which describes dependence of the mixture ionization coefficient on temperature. When there was a thin insulating film on the cathode the model took into account that positive charges are accumulated on its surface during the discharge. They generate an electric field in the film sufficient for the field emission of electrons from the metal substrate of the electrode into the insulator and some of them can overcome the potential barrier at the film outer boundary and go out in the discharge volume improving emission characteristics of the cathode.Calculations showed that at a temperature decrease the electric field strengthes in the discharge gap and the voltage in it are increased due to reduction of the saturated mercury vapor density in the mixture followed by the decrease of its ionization coefficient. Existence of a thin insulating film on the cathode surface results in an increase of the cathode effective secondary electron emission yield which compensates the reduction of the mixture ionization coefficient value.The results of discharge characteristics modeling demonstrate that in case of the cathode with an insulating film the discharge ignition becomes possible at a lower inter-electrode voltage. This ensures outdoor mercury lamp turning on at a reduced supply voltage and increases its reliability under low ambient temperatures.